Are nurse-led chemotherapy clinics really nurse-led? An ethnographic study. (April 2017) - Farrell, Carole; Walshe, Catherine; Molassiotis, Alex
Abstract: Background: The number of patients requiring ambulatory chemotherapy is increasing year on year, creating problems with capacity in outpatient clinics and chemotherapy units. Although nurse-led chemotherapy clinics have been set up to address this, there is a lack of evaluation of their effectiveness. Despite a rapid expansion in the development of nursing roles and responsibilities in oncology, there is little understanding of the operational aspects of nurses' roles in nurse-led clinics. Objectives: To explore nurses' roles within nurse-led chemotherapy clinics. Design: A focused ethnographic study of nurses' roles in nurse-led chemotherapy clinics, including semi-structured interviews with nurses. Settings: Four chemotherapy units/cancer centres in the UK Participants: Purposive sampling was used to select four cancer centres/units in different geographical areas within the UK operating nurse-led chemotherapy clinics. Participants were 13 nurses working within nurse-led chemotherapy clinics at the chosen locations. Methods: Non-participant observation of nurse-led chemotherapy clinics, semi-structured interviews with nurse participants, review of clinic protocols and associated documentation. Results: 61 nurse-patient consultations were observed with 13 nurses; of these 13, interviews were conducted with 11 nurses. Despite similarities in clinical skills training and prescribing, there were great disparities between clinics run by chemotherapy nurses and those run by advanced nurse practitioners. This included the number of patients seen within each clinic, operational aspects, nurses' autonomy, scope of practice and clinical decision-making abilities. The differences highlighted four different levels of nurse-led chemotherapy clinics, based on nurses' autonomy and scope of clinical practice. However, this was heavily influenced by medical consultants. Several nurses perceived they were undertaking holistic assessments, however they were using medical models/consultation styles, indicating medicalization of nurses' roles. Conclusions: Four different levels of nurse-led chemotherapy clinics were identified, illustrating disparities in nurses' roles. Although clinics are run by nurses they are often controlled by medical consultants, which can reduce nurses' autonomy and negatively impact on patient care.